2022
DOI: 10.5194/hess-2022-334
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hybrid forecasting: using statistics and machine learning to integrate predictions from dynamical models

Abstract: Abstract. Hybrid hydroclimatic forecasting systems employ data-driven (statistical or machine learning) methods to harness and integrate a broad variety of predictions from dynamical, physics-based models – such as numerical weather prediction, climate, land, hydrology and Earth system models – into a final prediction product. They are recognised as a promising way of enhancing prediction skill of meteorological and hydroclimatic variables and events, including rainfall, temperature, streamflow, floods, drough… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 133 publications
0
18
0
Order By: Relevance
“…We used a statistical-dynamical framework (Slater et al, 2022) to predict multiyear average winter (DJFM) high flows in the UK using precipitation and temperature. Decadal climate predictions are currently only publicly available as monthly aggregates.…”
Section: Flood Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used a statistical-dynamical framework (Slater et al, 2022) to predict multiyear average winter (DJFM) high flows in the UK using precipitation and temperature. Decadal climate predictions are currently only publicly available as monthly aggregates.…”
Section: Flood Predictionmentioning
confidence: 99%
“…Hybrid methods have several advantages compared to dynamical methods. They are computationally efficient, and can integrate a wide variety of nonstationary predictor variables, including climate forecasts, large-scale climate indices, and teleconnections (Slater et al, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Third, to assess future changes in crop yields, we drive the same multiple regression model with the bias-corrected projections of the same variables, computed from the 12 mem-bers of the UKCP Local simulations (i.e. we employ a hybrid approach; see Slater et al, 2022). This approach allows us to fuse together the data-driven regression model with the meteorological simulations for higher greenhouse gas emissions.…”
Section: Statistical Approachmentioning
confidence: 99%
“…Some studies for instance use Canonical Correlation Analysis (CCA) to relate observed SST in the Atlantic and Pacific oceans to regional rainfall, demonstrating the important role SST fields play in rainfall over Central America (Giannini et al ., 2000; Alfaro, 2007; Maldonado et al ., 2013; 2016; 2017; Alfaro et al ., 2016a), including for predictions of low‐ and high‐rainfall events (e.g., rainfall above the 80th and below the 10th percentiles of the monthly climatology; Maldonado et al ., 2013). Hybrid methods then combine dynamic and statistical methods (Slater et al ., 2022). Some hybrid methods generate indirect rainfall forecasts by extracting related variables (e.g., SST) from the GCMs and then statistically translate those values to target variables (e.g., Alfaro et al ., 2018; Strazzo et al ., 2019; Colman et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%